A Review on the Effects of Introducing CNTs in the Modification Process of Electrochemical Sensors - Beitollahi, Hadi; Movahedifar, Fahimeh; Tajik, Somayeh; Jahani, Shohreh (Electroanalysis (New York, N.Y.), 2019)
This review summarizes some developments in the fabrication of modified sensors and biosensors through the incorporating the carbon nanotubes (CNTs) in their modification ingredients. A large number of papers have paid attention towards the application of carbon nanotubes (CNTs) as electrode constituents and studied its electrochemical behavior. Here, we survey the achievements in the detection of various substances with high selectivity and sensitivity provided using CNTs based electrodes. Moreover, modified electrodes by CNTs have demonstrated the electrocatalytic features and higher sensitivity in detection of analytes. The improved characteristics arises from the large surface area and good conductivity of CNTs. However, it should be considered that the use of single walled carbon nanotubes (SWCNTs) or multi‐walled carbon nanotubes (MWCNTs), the presence of impurities, and the chemical procedures adopted are effective on the performance of the modified sensors.